IDENTIFIKASI KEMAMPUAN SISWA SMP DALAM MENJELASKAN IDE MATEMATIS DENGAN GAMBAR DAN ALJABAR BERDASARKAN TEORI MASON, BURTON, DAN STACEY - Shofiy Hanifah; Syamsuri Syamsuri; Aan Subhan Pamungkas (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to describe student’s skills in explaining mathematical ideas using pictures and algebra based on Mason, Burton, and Stacey theory to solve a polyhedral problem. This type of research is a qualitative descriptive study. The subject of this research is grade IX students of SMPN 7 Kota Serang. Data were collected by test and interview methods. The analysis technique used is using the theory of Mason, Burton, and Stacey which include specializing, generalizing, conjecturing, and convincing. The results of this research showing that the student’s skills in explaining mathematical ideas using pictures and algebra which can be classified into three types of answers, namely; 1) incomplete picture answer type where students cannot fulfill the thinking stage of specializing, generalizing, conjecturing, and convincing, 2) semi-complete picture answer type where students can fulfill the thinking stage of specializing, but difficult for fulfill the thinking stage of generalizing, conjecturing, and convincing, 3) complete picture answer type where students can fulfill the thinking stage of specializing, generalizing, and conjecturing, but still difficult for fulfill the thinking stage of convincing. These results are expected to be the teacher’s consideration in carrying out the learning process in the classroom, in determining methods and teaching materials, which are expected to be able to improve student’s skills and accuracy.